Pengembangan Buku Cerita Bergambar Berbasis Lingkungan Hidup pada Pembelajaran Tematik di Kelas II SD/MI - Ayu Nur Shawmi; Nurhaidah Widiani; Afni Novita Dewi (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2021)
This research is motivated by the learning media carried out in schools that look less effective and less attractive.Because learning in the classroom does not use alternative media other than thematic books. From the existing problems, environmental-based picture story books were developed with the aim of (1) being able to produce picture story books with the help of correl draw applications and Photoshop soft ware. (2) knowing how appropriate the picture book media is. (3) to determine the feasibility of validation response to the developed media. This type of research is Research and Development (R&D) by using the steps of the research and development method according to Borg and Gall, modified by Sugiyono. The stages in research and development are potential and problems, collecting data, product design, product validation, product revision, product testing, and product revision. The results of the validation on picture story books by linguists obtained an average percentage of 90% with very feasible criteria, material experts obtained an average percentage of 97% with very feasible criteria, media experts obtained an average percentage of 92% with very feasible criteria. The assessment on the response of educators obtained an average percentage of 99% with very feasible criteria, and students' responses to small-scale trials at Wates State Elementary School in Central Lampung obtained an average percentage of 90% with very feasible criteria, as well as large-scale trials at schools in MI Al-Hikmah Bandar Lampung get an average percentage of 89% with very decent criteria. It was concluded that the environmental-based storybook with the help of correl draw applications and Photoshop soft ware for thematic learning subjects of class II SD / MI on the theme of caring for animals and plants developed were suitable for use as learning media. Penelitian ini dilatar belakangi oleh media pembelajaran yang dilaksanakan di sekolah terlihat kurang efektif dan kurang menarik. Dari pemasalahan yang ada buku cerita bergambar dibuat kemudian dikembangkan menjadi buku cerita berbasis lingkungan hidup dengan tujuan untuk (1) dapat menghasilkan produk buku cerita bergambar dengan bantuan aplikasi correl draw dan soft ware potoshop. (2) mengetahui bagaimana kelayakan media buku cerita bergambar. (3) untuk mengetahui respon kelayakan validasi terhadap media yang dikembangkan. Jenis penelitian ini adalah Reseach and Development (R&D) dengan menggunakan langkah-langkah metode penelitian dan pengembangan menurut Borg and Gall yang dimodifikasi oleh Sugiyono. Adapun tahapan dalam penelitian dan pengembangan yaitu potensi dan masalah, mengumpulkan data, desain produk, validasi produk, revisi produk, uji coba produk, dan revisi produk. Hasil validasi pada buku cerita bergambar oleh ahli bahasa memperoleh rata-rata persentase 90% dengan kriteria sangat layak, ahli materi memperoleh rata-rata persentase 97% dengan kriteria sangat layak, ahli media memperoleh rata-rata persentase 92% dengan kriteria sangat layak. Penilaian pada respon pendidik memperoleh rata-rata persentase 99% dengan kriteria sangat layak, dan respon peserta didik pada uji coba skala kecil di Sekolah Dasar Negeri Wates Lampung Tengah memperoleh rata-rata persentase 90% dengan kriteria sangat layak, serta uji coba skala besar pada sekolah di MI Al- Hikmah Bandar Lampung memperoleh rata-rata persentase 89% dengan kriteria sangat layak. Disimpulkan bahwa buku cerita begambar berbasis lingkungan hidup dengan bantuan aplikasi correl draw dan soft ware potoshop mata pembelajaran tematik kelas II SD/MI pada tema merawat hewan dan tumbuhan yang dikembangkan layak digunakan sebagai media pembelajaran.